PENGARUH PRICE DISCOUNT DAN IN-STORE DISPLAY TERHADAP KEPUTUSAN IMPULSE BUYING PADA PRODUK MINISO - Ilham Sonata (JRMB (Jurnal Riset Manajemen & Bisnis), 2019)
In the era of globalization of business competition that is increasingly advanced and continues to increase, the pattern of people’s lives is predicted to experience significant changes. Excellence in this competition is mainly price discounts that can create consumer interest.This study aims to determine how much influence price discount has on impulse buying decisions, the effect of in-store displays on impulse buying decisions and the effect of price discounts and joint in-store displays on the decision on impulse buying on Miniso products.This study uses quantitative methods. This research was carried out on Miniso in Medan. The time of the study was conducted in December 2018 to Maret 2019. The population in this study could not ensure consumers who made impulsive purchases in Miniso Sun Plaza Medan and sample in this study were 96 respondents. As a research sample and sampling technique using a non probability sampling method that is by purposive sampling. Data analysis techniques used are multiple linear regression.Based on the results of the regression coefficient at the price discount of 0.305 with the value of tcount of 4.461 and the regression coefficient value in the in-store display of 0.323 with the value of tcount 3.842. Value the F test, the calculated value is 39.621 Ftable 3.09 and the significant level for the F test is 0.000 0.05. It means that price discount and in-store display have a positive and significant effect on the decision of impulse buying.